Low-dose sodium acetate-mediated energy compensation stabilizes oxygen-limited urea hydrolysis coupled with partial nitritation/anammox for high-strength urea wastewater treatment - Meng Yang; Yonggan Li; Yongxing Chen; Yu Zhang; Yasong Wang; Qingyu Liu; Simin Lu; Xiaojun Wang (Bioresource Technology, 2026)

Willow-Leaf copper MOF networks for efficient oil-water separation and anti-microbial adhesion - Meng Xu; Simin He; Yu Wang; Lang Wei; Jinying Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Icing distribution characteristics on wind turbine blades and their implications for anti-/de-icing element layout - Simin Li; Lixin Yang; Yiqi Liu; Haojie Zhang; Jiale Yu; Yuchen Zhou (Cold Regions Science and Technology, 2026)

Corrigendum to “Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence” [Chem. Eng. J. 524 (2025) 169152] - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Acetochlor disrupts the maternal effect of food restriction in lizards (Eremias argus): Evidence from intergenerational growth and embryonic development - Yue Zhang; Yufan Nie; Simin Yu; Yuping Liu; Hao Yang; Jiajing Sun; Dier Song; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Journal of Hazardous Materials, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Acute exercise activates hepatic Nrf2 signaling by ROS, AMPK and epinephrine to protect against acute liver injuries - Simin Yang; Ranting Zhao; Li Lei; Xiangbo An; Jiangli Xu; Han Xu; Jiahui Wang; Han Xiao; Youyi Zhang; Xiaoda Yang; Siwang Yu (Toxicology and Applied Pharmacology, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Seasonal jet stream dominates spatiotemporal heterogeneity of dry-wet status in arid Central Asia since the Holocene - Simin Peng; Yu Li; Zhansen Zhang; Zhi Zhang; Yong Ge (Global and Planetary Change, 2026)

Assessment of the semipermeable membrane effect of illite and montmorillonite on dissolved thallium diffusion - Yu Liu; Simin Hu; Lezhang Wei; Dinggui Luo; Tangfu Xiao (Engineering Geology, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Role of heterogeneity of counter-diffusional biofilm on microaeration-assisted for nitrophenol degradation: Metabolic pathways and microbial mechanisms - Zhuowei Zhang; Simin Li; Jing Guo; Yin Yu; Wenhao Hou; Jingye Yang (Journal of Water Process Engineering, 2026)

AI-assisted discovery of dual antioxidant and ACE-inhibitory peptides from Hericium erinaceus - Rongheng Chen; Jiahao Yu; Simin Feng; Ping Shao (Food Chemistry, 2026)

Efficacy and safety of vunakizumab between super responders and non-super responders of patients with moderate-to-severe plaque psoriasis: a post-hoc exploratory analysis of a phase III trial - Ougen Liu; Caixia Kou; Simin Yu; Huizhong Hu; Xiaoxiao Chen; Meiying Jiang; Shifeng Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of porcine-derived atypical intestinal pathogenic Escherichia coli reveals to a hidden threat of extraintestinal infection - Zhonghao Chen; Simin Lv; Shiyu Zhang; Yong Yu; Jiale Ma; Huochun Yao; Xinming Pan (Veterinary Microbiology, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Fault diagnosis of Autonomous Underwater Vehicle thruster based on semi supervised interference suppression network - Hongchao Wang; Guoqing Xue; Bowen Liu; Jianwen Jiang; Li Yu; Simin Li; Wenliao Du (Ocean Engineering, 2025)

Hydrological and geochemical controls on CO2 and CH4 emissions from a temperate glacier-fed river on the Tibetan Plateau - Zhiheng Du; Tao Pu; Fangping Yan; Yu Zhu; Zizhen Jin; Lei Wang; Simin Xie; Changlian Tao; Shijin Wang; Shiyin Liu; Cunde Xiao (Journal of Hydrology, 2025)

Scalable engineering of sCNC microcapsules for synergistic weed control and environmental safeguarding - Xile Deng; Liang Li; Simin Yu; Yanan Deng; Zhanghua Zeng; Lianyang Bai (Chemical Engineering Journal, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2025)

Development of fluorine-free superhydrophobic antibacterial and antifouling coatings: A multifunctional composite system for biomedical materials and metal protection - Meng Xu; Simin He; Yu Wang; Rongkai Li; Lang Wei; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Nitrogen and phosphorus preferring photogranules regulate COD/TN by carbon fixation through superposition of Chlorophyta, Cyanobacteria and Chloroflexi - Chenghang Tu; Zhensheng Xiong; Mengsha Dai; Simin Liao; Li Xie; Binghong Chen; Helen Yu (Chemical Engineering Journal, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Hibernating male lizards (Eremias argus) cleverly respond to insecticide exposure and warming temperatures: survival rate and physical condition cannot coexist - Yue Zhang; Simin Yu; Yufan Nie; Yuping Liu; Zikang Wang; Ning Zhang; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2025)

Glyphosate threatens lizard adaptation to warming: Disruption to maternal effects - Simin Yu; Yue Zhang; Yufan Nie; Zikang Wang; Yuping Liu; Luyao Zhang; Rui Liu; Jinling Diao (Journal of Hazardous Materials, 2025)

Enhanced extraction of microplastics from terrestrial animal intestinal tissues via optimized fenton oxidation - Simin Yu; Jiaqi Chen; Zhanao Zhang; Yanping Zhao; Yan Zhang (Journal of Hazardous Materials, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Mendelian randomization and multi-omics analysis identify C4A as a critical protective biomolecule in head and neck squamous cell carcinoma - Ziqing Yang; Xinhui Qiu; Anquan Ma; Chenyang Wu; Xiaoyang Zong; Yifei Nie; Simin Zhan; Haoran Yang; Chengyuan Zhang; Huilu Song; Xu Wang; Zhihong Zhang; et al. (Chemical Engineering Journal, 2025)

Seasonal variation and environmental regulation mechanisms of energy fluxes and energy allocation in dune and meadow ecosystems - Simin Zhang; Tingxi Liu; Lina Hao; Limin Duan; Xin Tong; Yongzhi Bao; Yixuan Wang; Yu Gong; Wei Zhang (CATENA, 2025)

Water-stabilized perovskite CsPbBr3/CsPb2Br5 for high-sensitivity fluorescence “on-off-on” recognition and cell imaging - Simin He; Rongkai Li; Meng Xu; Yu Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Selective recovery of rare earth elements from mine wastewater using the magnetic zeolite prepared by rare earth tailings - Jianhui Zhang; Jianchen Cheng; Guizhou Xu; Xuechao Hou; Zhifei Yu; Wei Liu; Yalan Zhang; Jianxin Chen; Jiahao Yang; Mengting Wu; Wanqing Yang; Simin Li; et al. (Chemical Engineering Journal, 2025)

Beneficial reuse of pyrolytic post-remediation soil to activate persulfate oxidation and avoid exposure of environmentally persistent free radicals - Mingxin Wang; Simin Song; Wei Liu; Zhenzhen Yu (Process Safety and Environmental Protection, 2025)

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Adaptive Surrogate Model Assisted Swarm Intelligence for Parameter Inversion of complex hydrological models - Guhan Li; Peng Shi; Simin Qu; Lingzhong Kong; Xiaohua Xiang; Qian Yang; Yu Qiao; Shiyu Lu (Environmental Modelling & Software, 2025)

Remediation of thallium-contaminated groundwater using magnetic illite–biochar: Structural characteristics, performance and mechanisms - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2025)

Effects of acetochlor on the interaction between Scenedesmus and Microcystis: Integrated perspectives on toxicity, biotransformation, and competition strategies - Zikang Wang; Simin Yu; Yufan Nie; Yue Zhang; Yuping Liu; Shanshan Li; Wensheng Xiang; Jinling Diao (Journal of Hazardous Materials, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Mobilization of phosphorus in sediments of eutrophic lakes induced by elevated sulfate levels - Lanqing Zhang; Miaotong Yu; Simin Yu; Huaizhi Chen; Mengmeng Xiao; Guoxiang Wang; Yanping Zhao (Science of The Total Environment, 2024)

Akt inhibitors prevent CyHV-2 infection in vitro - Yu Song; Ye Zhang; Simin Xiao; Pengfei Li; Liqun Lu; Hao Wang (Fish & Shellfish Immunology, 2024)

Simultaneously enhancing the EMI shielding performances and mechanical properties of structure–function integrated CF/PEEK composites via chopped ultra-thin carbon fiber tapes and interfacial engineering with MXene - Simin Zhang; Jinze Cui; Xingwen Kuang; Mingbin Lai; Yutai Luo; Feng Bao; Jiali Yu; Caizhen Zhu; Jian Xu; Huichao Liu (Chemical Engineering Journal, 2024)

How does the biochar-supported sulfidized nanoscale zero-valent iron affect the soil environment and microorganisms while remediating cadmium contaminated paddy soil? - Wenjing Xue; Siqi Wen; Xinyu Chen; Yu Wang; Simin Qian; Yiyun Wu; Rongrong Ge; Yang Gao; Yiqun Xu (Environmental Geochemistry and Health, 2024)

An innovative in situ solvent generation enhanced SAGD technique: Mechanism analysis based on numerical simulation - Simin Yang; Siyuan Huang; Qi Jiang; Guanchen Jiang; Xiang Zhou; Chunsheng Yu (Fuel, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Recent advances in clay minerals for groundwater pollution control and remediation - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Environmental Science and Pollution Research, 2024)

Effects of Lipid on the Formation of Heterocyclic Aromatic Amines and Advanced Glycation End Products in Thermally Processed Fish - Xi Chen; Ruichun Wang; Haixia Yu; Yingying Huang; Simin Zhang (Journal of Aquatic Food Product Technology, 2024)

Differential influences of forest floor-pyrolyzed biochar-derived and leached dissolved organic matter interaction with natural iron-bearing minerals in forest subsoil on the formation of mineral-associated soil organic matter - Caisheng Li; Hua Wang; Simin Li; Hengkuan Ji; Xuefeng Yu; Dengfeng Wang; Zhengwei Hou; Quanchao Wang; Zhipeng Wu; Xueren Chang; Jinyi Huang; Xilong Wang (Science of The Total Environment, 2024)

Effect of acetochlor on the symbiotic relationship between microalgae and bacteria - Zikang Wang; Simin Yu; Yufan Nie; Ran Liu; Wentao Zhu; Zhiqiang Zhou; Yongqiang Ma; Jinling Diao (Journal of Hazardous Materials, 2024)

Nano-selenium repaired the damage caused by fungicides on strawberry flavor quality and antioxidant capacity by regulating ABA biosynthesis and ripening-related transcription factors - Yuping Liu; Rui Liu; Feifei Li; Simin Yu; Yufan Nie; Jia-Qi Li; Canping Pan; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Pesticide Biochemistry and Physiology, 2024)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

Environmental, social, and governance (ESG) performance and financial outcomes: Analyzing the impact of ESG on financial performance - Simin Chen; Yu Song; Peng Gao (Journal of Environmental Management, 2023)

Hydrogeochemical evolution of groundwater impacted by acid mine drainage (AMD) from polymetallic mining areas (South China) - Yu Liu; Xianming Xie; Song Wang; Simin Hu; Lezhang Wei; Qihang Wu; Dinggui Luo; Tangfu Xiao (Journal of Contaminant Hydrology, 2023)

Interspecific insights into direct and indirect effects of acetochlor on interactions between daphnids and microalgae: Toxic, trophic, and grazer-infochemical responses - Zikang Wang; Simin Yu; Yufan Nie; Ning Zhang; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2023)

Applicability assessment of five evapotranspiration models based on lysimeter data from a bioretention system - Wenlong Zhang; Moyuan Yang; Shouhong Zhang; Lei Yu; Fei Zhao; Duwei Chen; Simin Yang; Hualin Li; Sunxun Zhang; Ruixian Li; Jianjun Zhang (Ecological Engineering, 2023)

Bioaugmentation of Cd(II) removal in high-salinity wastewater by engineered Escherichia coli harbouring EC20 and irrE genes - Simin Zong; Hui Yun; Xuan Yu; Yue He; Aman Khan; Haibo Tang; Si Li; Wenxue Wang; Xiangkai Li (Journal of Cleaner Production, 2023)

Distribution and Characteristics of Microplastics in Agricultural Soils around Gehu Lake, China - Jingcheng Liang; Xian Chen; Simin Zha; Xingming Chen; Yijun Yu; Xiaotong Duan; Yiran Cao; Yuechang Liang (Water, Air, & Soil Pollution, 2023)

Time-scale effects in human-nature interactions, regionally and globally - Yu Li; Mingjun Gao; Zhansen Zhang; Yuxin Zhang; Simin Peng (Journal of Geographical Sciences, 2023)

Hydrogeochemistry of groundwater surrounding a pyrite mine in southern China: Assessment of the diffusive gradients in thin films technique for in situ monitoring - Yu Liu; Lezhang Wei; Hongmei Deng; Simin Hu; Xianming Xie; Dinggui Luo; Tangfu Xiao (Journal of Hydrology, 2023)

The combined effects of atrazine and warming on environmental adaptability in lizards (Eremias argus) from the perspective of a life-history traits trade-off: Gender differences in trade-off strategies may reverse mortality risk - Yufan Nie; Zikang Wang; Simin Yu; Luyao Zhang; Rui Liu; Yuping Liu; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2023)

Design, synthesis and mechanism study of novel natural-derived isoquinoline derivatives as antifungal agents - Wei Chen; Rui Zhang; Yang Chen; Pingbing Yu; Yuxin Lan; Haojian Xu; Simin Lei (Molecular Diversity, 2023)

Transcriptome analysis reveals self-redox mineralization mechanism of azo dyes and novel decolorizing hydrolases in Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Simin Zong; Aman Khan; Wenxue Wang; Hui Yun; Peng Zhang; Toshiro Shigaki; Yitian Fang; Huawen Han; Xiangkai Li (Environmental Pollution, 2023)

Identification and validation of quantitative trait loci for fertile spikelet number per spike and grain number per fertile spikelet in bread wheat (Triticum aestivum L.) - Cheng Jiang; Zhibin Xu; Xiaoli Fan; Qiang Zhou; Guangsi Ji; Liangen Chen; Qin Yu; Simin Liao; Yun Zhao; Bo Feng; Tao Wang (Theoretical and Applied Genetics, 2023)

Utilization of ovalbumin-propylene glycol alginate complex system for superior foam: The effect of pH-driven phase behavior - Xinyue Zhang; Zizhen Sun; Qi Zeng; Haobo Jin; Simin Wang; Yongguo Jin; Yu Hu; Zhaoxia Cai (Food Hydrocolloids, 2023)

Reduction of metronidazole in municipal wastewater and protection of activated sludge system using a novel immobilized Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Wenxue Wang; Saurabh Kulshrestha; Peng Zhang; Muhammad Usman; Simin Zong; Mian Gul Hilal; Yitian Fang; Huawen Han; Xiangkai Li (Bioresource Technology, 2023)

MicroRNA-196a-5p overexpression in Wharton’s jelly umbilical cord stem cells promotes their osteogenic differentiation and new bone formation in bone defects in the rat calvarium - Yantong Wang; Simin Zhang; Haoqing Yang; Yangyang Cao; Dianqin Yu; Yingchu Zhao; Yu Cao (Cell and Tissue Research, 2022)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

Dynamic relationship between meteorological conditions and air pollutants based on a mixed Copula model - Simin He; Zhiyao Li; Wenjie Wang; Mingxing Yu; Liangpo Liu; Md Nur Alam; Qian Gao; Tong Wang (International Journal of Climatology, 2021)
Many methods have been developed to verify the correlation between meteorological conditions and air pollutants; however, all have limitations that lead to biased or incomplete conclusions. Hence, improved methods are urgently required to describe this correlation comprehensively and accurately. In this study, we demonstrated the ability of the Copula function to apply time‐varying correlations between meteorological factors and atmospheric pollutants. A mixed Copula model was constructed using meteorological monitoring data for Beijing and Guangzhou from 2014 to 2019 to dynamically analyse the correlation characteristics and tail dependence between these factors. We then performed a correlation analysis for the data from the average, lower, and upper tails to obtain a more accurate and comprehensive correlation description. Dynamic analysis results demonstrated significant seasonal fluctuations between meteorological conditions and pollutants relationships. Moreover, the correlation coefficient variations differ according to their average and tail values. High humidity is more likely to be accompanied by increased NO 2 compared with average summer humidity. Our proposed model represents a novel application of the Copula function for determining the factors influencing air pollution. This model emphasizes the tail dependence between meteorological conditions and air pollutant concentrations and can be used to guide more targeted prevention and control strategies.

Spatial study of particulate matter distribution, based on climatic indicators during major dust storms in the State of Arizona - Amin Mohebbi; Fan Yu; Shiqing Cai; Simin Akbariyeh; Edward J. Smaglik (Frontiers of Earth Science, 2021)

A continuous simulation of Holocene effective moisture change represented by variability of virtual lake level in East and Central Asia - Yu Li; Yuxin Zhang; Xinzhong Zhang; Wangting Ye; Lingmei Xu; Qin Han; Yichan Li; Hebin Liu; Simin Peng (Science China Earth Sciences, 2020)

Isolation, structure elucidation, tyrosinase inhibitory, and antioxidant evaluation of the constituents from Angelica dahurica roots - Penghua Shu; Junping Li; Yingying Fei; Huiqing Zhu; Mengzhu Yu; Anqi Liu; Haoying Niu; Simin Zou; Xialan Wei; Zhiyu Ju; Zhihong Xu (Journal of Natural Medicines, 2020)

Dibenzoylmethane Protects Against CCl4-Induced Acute Liver Injury by Activating Nrf2 via JNK, AMPK, and Calcium Signaling - Mingnan Cao; Huixia Wang; Limei Guo; Simin Yang; Chun Liu; Tin Oo Khor; Siwang Yu; Ah-Ng Kong (The AAPS Journal, 2017)

Temporal 18 O and deuterium variations in hydrologic components of a small watershed during a typhoon event - Simin Qu; Yifan Wang; Minmin Zhou; Han Liu; Peng Shi; Zhongbo Yu; Long Xiang (Isotopes in Environmental and Health Studies, 2017)

Evaluating Infiltration Mechanisms Using Breakthrough Curve and Mean Residence Time - Qu Simin; Wang Tao; Bao Weimin; Shi Peng; Jiang Peng; Zhou Minmin; Yu Zhongbo (Water Resources Management, 2013)